A novel urea coated with pine oleoresin for enhancing yield and nitrogen uptake by maize crop. (9th November 2016) - Kundu, S.; Adhikari, Tapan; Coumar, M. Vassanda; Rajendiran, S.; Saha, J. K.; Rao, A. Subba; Rathore, Gopal
ABSTRACT: A study was conducted with maize in Vertisol, Inceptisol, Alfisol and Aridisol to evaluate the efficacy of the pine oleoresin coated urea fertilizers (coated with 1.25, 2.50, 3.75 and 5.00% pine oleoresin). Significant increase in biomass yield was observed in all the soils when urea was coated with pine oleoresin at 3.75% or more. All the pine oleoresin coated urea in Inceptisol and Aridisol; and 3.75% and 5% pine oleoresin coated urea in Vertisol and Alfisol significantly increased nitrogen (N) uptake as compared to uncoated urea. Nitrogen use efficiency increased from 19.34% to 32.80% in Vertisol, 13.06% to 28.27% in Alfisol, 13.87% to 23.86% in Inceptisol and 10.68% to 20.23% in Aridisol, as a result of coating urea with pine oleoresin. Thus the results indicate that there is a beneficial effect of coating urea with pine oleoresin with respect to yield, N uptake and use efficiency in maize crop.